Klokwerk + study protocol: An observational study to the effects of night–shift work on body weight and infection susceptibility and the mechanisms underlying these health effects. (December 2016) - Loef, Bette; van Baarle, Debbie; van der Beek, Allard; van Kerkhof, Linda; van de Langenberg, Daniëlla; Proper, Karin
Abstract Background Night–shift work may cause severe disturbances in the worker's circadian rhythm, which has been associated with the onset of health problems and diseases. As a substantial part of the workforce is exposed to night–shift work, harmful aspects of night–shift work should not be overlooked. The aim of the Klokwerk + study is to study the effects of night–shift work on body weight and infection susceptibility and the mechanisms underlying these health effects. First, we will study the relation between night–shift work exposure and body weight and between night–shift work exposure and infection susceptibility. Second, we will examine the mechanisms linking night–shift work exposure to body weight and infection susceptibility, with a specific focus on sleep, physical activity, diet, light exposure, vitamin D level, and immunological factors. Lastly, we will focus on the identification of biomarkers for chronic circadian disturbance associated with night–shift work. Methods/design The design of this study is a prospective observational cohort study consisting of 1, 960 health care workers aged 18–65 years. The study population will consist of a group of night–shift workers and an equally sized group of non–night–shift workers. During the study, there will be two measurement periods. As one of the main outcomes of this study is infection susceptibility, the measurement periods will take place at approximately the first (September/October) (T0) and the last month (April/May) (T1, after 6 months) of the flu season. The measurements will consist of questionnaires, anthropometric measurements, a smartphone application to determine infection susceptibility, food diaries, actigraphy, light sensors, and blood sample analyses. Discussion The Klokwerk + study will contribute to the current need for high–quality data on the health effects of night–shift work and its underlying behavioral and physiological mechanisms. The findings can be the starting point for the development of interventions that prevent negative health effects caused by night–shift work. In addition, the identification of biomarkers indicative of loss of homeostasis due to circadian disturbance may be an important asset in monitoring the effects of such interventions.